2015
DOI: 10.1111/dmcn.12992
|View full text |Cite
|
Sign up to set email alerts
|

Do research studies in the UK reporting child neurodevelopment adjust for the variability of assessors: a systematic review

Abstract: AIM Neurodevelopment is a key outcome for many childhood trials and observational studies. Clinically important decisions may rest on finding relatively small differences in neurodevelopment between groups receiving complex and costly interventions. Our purpose was to determine whether studies which measure neurodevelopment report the numbers, training, and auditing of assessors and, for multiple assessor studies, whether the results were adjusted and if so by which method?METHOD Electronic searches were condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Study designs frequently maximise participant numbers in order to investigate the possibility of subtle neuropsychological differences, which may be important to long-term outcomes, and because good follow-up rates are important for data validity in longitudinal studies. This has logistical implications, because many studies will require multiple assessors to conduct the assessments, with some potentially problematic consequences, as elucidated in this issue by Khalid et al 1 Standardised assessments are chosen for research partly because the important issues of reliability and validity are included in the assessment design, with assessment manuals incorporating instructions on how to conduct an assessment to meet standardisation requirements. However, there is inevitably some variation in interpersonal exchange between different assessors and study participants.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Study designs frequently maximise participant numbers in order to investigate the possibility of subtle neuropsychological differences, which may be important to long-term outcomes, and because good follow-up rates are important for data validity in longitudinal studies. This has logistical implications, because many studies will require multiple assessors to conduct the assessments, with some potentially problematic consequences, as elucidated in this issue by Khalid et al 1 Standardised assessments are chosen for research partly because the important issues of reliability and validity are included in the assessment design, with assessment manuals incorporating instructions on how to conduct an assessment to meet standardisation requirements. However, there is inevitably some variation in interpersonal exchange between different assessors and study participants.…”
mentioning
confidence: 99%
“…Khalid et al 1 found a low rate of reporting of assessor numbers, training and auditing, which may imply a laissezfaire attitude on the part of the authors, reflect a deference to word count, or result from an entrenched blind-spot in reporting. It cannot be assumed that good research practice was not followed.…”
mentioning
confidence: 99%
See 3 more Smart Citations